Clinical course of sub-centimeter-sized nodules detected during surveillance for hepatocellular carcinoma - Min, Yang Won (Baishideng Publishing Group Co., Limited, 2012)
AIM: To evaluate the outcome of sub-centimeter-sized nodules (SCSNs) detected during surveillance for hepatocellular carcinoma (HCC) in patients at risk. METHODS: We retrospectively analyzed a total of 142 patients with liver cirrhosis or chronic hepatitis B or C without a prior history of HCC in whom a SCSN was detected during HCC surveillance. We calculated the rate of HCC development from SCSNs in the study population and analyzed the differences in the baseline clinical characteristics and imaging features between the patients with SCSNs that eventually developed into HCC and patients with SCSNs that did not develop into HCC. RESULTS: During 667 person-years of follow-up, HCC developed in 33 patients. The calculated HCC development rate was 4.9% per year. The cumulative one-, two-, three- and five-year HCC development rates were 5.6%, 10.6%, 14.1% and 20.4%, respectively. Upon baseline comparison, the HCC group was older (54.4 ± 8.3 years vs 48.9 ± 9.4 years; P = 0.003) and had lower albumin levels (3.56 ± 0.58 g/dL vs 3.84 ± 0.55 g/dL; P = 0.012) and higher baseline alpha-fetoprotein (AFP) levels (8.5 ng/mL vs 5.4 ng/mL; P = 0.035) compared to the non-HCC group. Nodule pattern and initial radiologic diagnosis also differed between the two groups. Multivariate analysis revealed that age [P = 0.012, odds ratio (OR) =1.075, 95% confidence interval (CI) =1.016-1.137], sex (P = 0.009, OR = 3.969, 95% CI: 1.403-11.226), and baseline AFP level (P = 0.024, OR = 1.039, 95% CI: 1.005-1.073) were independent risk factors for developing HCC. CONCLUSION: The overall risk of HCC development in patients with SCSNs is similar to that in liver cirrhosis patients. Patients with these risk factors need to be closely monitored during follow-up.